Geoscience Medallist 1. Understanding the Holocene Closed-Basin Phases (Lowstands) of the Laurentian Great Lakes and Their Significance - Lewis, C.F.M. (Geoscience Canada, 2016)
The Laurentian Great Lakes are a chain of five large water bodies and connecting rivers that constitute the headwaters of the St. Lawrence River. Collectively they form one of the largest reservoirs of surface freshwater on the planet with an aggregate volume of >22,000 km3. Early interpretations of the postglacial lake history implicitly assumed that the Great Lakes always overflowed their outlets. A study of Lake Winnipeg which concluded that lack of water in a dry climate had dried that lake for millennia led to re-evaluation of the Great Lakes water-level history. Using the empirical information of glacioisostatic rebound derived from 14C-dated and uptilted Great Lake paleo-shorelines, a method of computation was developed to test the paradigm of continuous lake overflow. The method evaluated site and outlet uplift independently, and lowlevel indicators such as submerged tree stumps rooted beneath the present Great Lakes were found to be lower than the lowest possible corresponding basin outlet. Results confirmed the low-level, closed-basin hydrological status of the early Great Lakes. This status is consistent with paleoclimatic inferences of aridity during the early Holocene before establishment of the present patterns of atmospheric circulation which now bring adequate precipitation to maintain the overflowing lakes. In a sense, the early to middle Holocene phase of dry climate and low water levels is a natural experiment to illustrate the sensitivity of the Great Lakes to climate change in this era of global warming, should their climate shift to one much drier than present, or future major diversions of their waters be permitted. RÉSUMÉ Les Grands Lacs Laurentiens sont une chaine de cinq grandes étendues d’eau connectées par des rivières, constituant la source du Fleuve St-Laurent. Collectivement, ils forment un des plus grands réservoirs d’eau douce de surface de la planète avec un volume total de plus de >22,000 km3. Les premières interprétations de l’histoire postglaciaire des lacs supposaient implicitement que les Grands Lacs débordaient à leurs exutoires. Une étude du Lac Winnipeg, qui concluait qu’un déficit en eau durant un épisode de climat aride avait desséché le lac pendant des millénaires dans le passé, a mené à la réévaluation de l’histoire du niveau de l’eau des Grands Lacs. En utilisant des données empiriques du relèvement glacio-isostatique, dérivées de littoral anciens surélevés datés au 14C, une méthode de calcul a été développée pour tester le paradigme d’une décharge lacustre continue. La méthode a évalué le soulèvement des sites et des exutoires indépendamment, et il a été constaté que les indicateurs de bas niveau tels que des troncs d’arbres submergés, enracinés en dessous des Grands Lacs actuels, étaient en fait sous le niveau de l’exutoire correspondant le plus bas. Les résultats confirment le bas niveau et le statut de basin hydrologique fermé des Grand Lacs dans le passé. Ce statut est cohérent avec des évidences paléoclimatiques d’aridité au début de l’Holocène, avant l’établissement des modes de circulation atmosphérique actuels qui apportent des quantités de précipitation adéquates au maintien des décharges lacustres. Dans un sens, la période climatique aride du début et du milieu de l’Holocène, et les bas niveaux d’eau constituent une expérience naturelle qui illustre la sensibilité des Grands Lacs aux changements climatiques, pertinent dans le contexte actuel de réchauffement global, surtout s’il s’avérait que leur climat devienne plus aride que présentement, ou que des diversions majeures des eaux soient permises.